Desorption of phosphate in oxisols covered by humid brushland ( savannah). II. The reversibility of the phosphate adsorption isotherm with respect to the pH of the equilibrium solution - Leal, Jair Rocha; Velloso, Ary Carlos X. (Pesquisa Agropecuaria Brasileira, 2014)
Experiments were carried out in four oxisols under cerrado vegetation (savannah) to investigate the reversibility of the adsorption isotherm with respect to pH of the equilibrium solution. The adsorbed phosphate was apparently reversible with respect to pH value for the change from pH 4 to 7. Soils containing phosphate previously adsorbed showed a desorption of the order 14% to 28%, for the change from pH 4 to 7.